2022
DOI: 10.3389/fneur.2022.904722
|View full text |Cite
|
Sign up to set email alerts
|

Phase-dependent Brain Activation of the Frontal and Parietal Regions During Walking After Stroke - An fNIRS Study

Abstract: BackgroundRecovery of walking post-stroke is highly variable. Accurately measuring and documenting functional brain activation characteristics during walking can help guide rehabilitation. Previous work in this area has been limited to investigations of frontal brain regions and have not utilized recent technological and analytical advances for more accurate measurements. There were three aims for this study: to characterize the hemodynamic profile during walking post-stroke, to investigate regional changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Our findings are line with Li et al study, which demonstrated that the brain networks of acute stroke patients exhibit reduced cosmopolitan structure and fewer longrange connections compared to those of healthy individuals (57). Similar research has discovered a correlation between small-world characteristics in the inferior cerebral cortex region of RS and motor function among patients (58). Studies have demonstrated that there is an inverse relationship between motor function and the clustering coefficient of the brain network (35).…”
Section: Discussionmentioning
confidence: 67%
“…Our findings are line with Li et al study, which demonstrated that the brain networks of acute stroke patients exhibit reduced cosmopolitan structure and fewer longrange connections compared to those of healthy individuals (57). Similar research has discovered a correlation between small-world characteristics in the inferior cerebral cortex region of RS and motor function among patients (58). Studies have demonstrated that there is an inverse relationship between motor function and the clustering coefficient of the brain network (35).…”
Section: Discussionmentioning
confidence: 67%
“…fNIRS data were continuous sampled at 4.36 Hz through Aurora 1.4 (NIRx Medical Technologies, Berlin, Germany). The probe configuration for this experiment was similar to our previous studies [9,20,21] with 48 long separation channels (∼30-35 mm apart) and 8 short separation channels (8 mm apart). Two different distances were chosen to control for extracerebral systemic changes such as breathing, heartbeat, and mayer waves [22].…”
Section: Methodsmentioning
confidence: 98%
“…To date, the impact of stroke on functional activation changes with speed modulation is unknown. Previous studies have shown indications of asymmetric brain activations with greater ipsilesional prefrontal [9], contralesional sensorimotor [9,10], and contralesional posterior parietal [9] cortices relating to faster walking speeds poststroke. The changes in the amplitude of activation during walking at different speeds poststroke are also unclear.…”
Section: Introductionmentioning
confidence: 94%
“…The specific steps included ( Fig. 2 ): (1) Converting the original data into optical density; (2) Using principal component analysis (PCA) for signal filtering; (3) Using Motion standard deviation and spline interpolation methods to remove motion artifacts, and excluding stimuli that fall within the time points identified as motion artifacts from hemodynamic response function calculation [ 22 ]; (4) Using bandpass filtering (0.01 Hz–0.1HZ) to remove physiological noises such as respiration, heartbeat, blood pressure and baseline deviation; (5) Converting optical density to changes in blood oxygen concentration using the modified Beer-Lambert law (with a partial path length factor (PPF) of 6.0 [ 23 , 24 ]); (6) Eliminating irrelevant stimuli outside the defined variables; (7) Using the block-average method, with the average concentration in the first 5 s [ 25 , 26 ] before the task begins used as the baseline, and averaging the concentration for all sample points within the first 25 s post-task initiation; (8) For baseline correction, selecting the most sensitive HbO 2 index with a larger variation range and better signal-to-noise ratio to represent the hemodynamic changes in the brain region, and subtracting baseline HbO 2 from HbO 2 within 25 s post-task initiation for normalization [ 27 , 28 ]. The resulting △HbO 2 mean value represents the brain activation during the task.…”
Section: Methodsmentioning
confidence: 99%